Digital Transformation Impact: Pengaruh Digitalisasi terhadap Kinerja UMKM - Putri Intan Prastiwi; Arif Setiawan; Zaenal Mustofa; Nova Mei Indriyani; Nadia Putri (ITB AAS Indonesia Surakarta, 2026)
This study aims to analyze the effect of digital transformation on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Surakarta, particularly in the fashion, culinary, and creative economy sectors. The study examines four dimensions of digital transformation, namely business process transformation, business model transformation, domain transformation, and organizational/cultural transformation, and their influence on MSME performance. This research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 50 MSME owners selected using a non-probability sampling technique with purposive sampling method. Data analysis was conducted using Structural Equation Modeling–Partial Least Square (SEM-PLS). The results indicate that business process transformation, business model transformation, domain transformation, and organizational/cultural transformation have a positive and significant effect on MSME performance. Business process transformation was identified as the most dominant variable influencing MSME performance through operational digitalization, administrative automation, and technological integration. The findings demonstrate that digital transformation plays a strategic role in improving sales growth, productivity, profitability, and business competitiveness of MSMEs. The novelty of this study lies in the integration of four dimensions of digital transformation in analyzing MSME performance within the context of fashion, culinary, and creative economy sectors in Surakarta.